Two-way and anonymous heterogeneous signcryption scheme between PKI and IBC - Cai-fen WANG; Chao LIU; Ya-hong LI; Shu-fen NIU; Yu-lei ZHANG (Tongxin xuebao)
Exiting heterogeneous signcryption schemes which were between public key infrastructure (PKI) and identity-based cryptosystem (IBC) have some limitations.A new heterogeneous signcryption scheme between PKI and IBC was proposed.In the random oracle mode,the scheme ensured confidentiality and unforgeability on the basis of the assumption of computational Diffie-Hellman problem (CDHP),q-Diffie-Hellman inversion problem (q-DHIP) and bilinear Diffie-Hellman problem (BDHP).Simultaneously,the proposed scheme guaranteed unconnectedness and anonymity of the ciphertext.Compared with other heterogeneous schemes,the scheme achieved two-way signcryption,and it generated parameters without restrict,which was suitable for actual situations.Simulation tests show that proposed scheme is feasible.